2021
DOI: 10.3171/2019.12.jns193196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomical analysis between the minipterional and supraorbital approaches

Abstract: OBJECTIVEKeyhole approaches, namely the minipterional approach (MPTa) and the supraorbital approach (SOa), are alternatives to the standard pterional approach to treat lesions located in the anterior and middle cranial fossae. Despite their increasing popularity and acceptance, the indications and limitations of these approaches require further assessment. The purpose of the present study was to determine the differences in the area of surgical exposure and surgical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Martínez-Pérez et al showed that, for aneurysm surgery, both the area of exposure and surgical freedom afforded by the MP approach were statistically greater than those provided by SO craniotomy. 19 However, in their analysis, SO craniotomy did not extend laterally to the superior temporal line. Another study by the same group compared the MP approach with an "extended SO" approach with a burr hole at the keyhole; this modification is essentially the same as the skin incision and craniotomy used by us.…”
Section: Clinical Use Of So Versus Mp Routes Compared With Anatomical Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…Martínez-Pérez et al showed that, for aneurysm surgery, both the area of exposure and surgical freedom afforded by the MP approach were statistically greater than those provided by SO craniotomy. 19 However, in their analysis, SO craniotomy did not extend laterally to the superior temporal line. Another study by the same group compared the MP approach with an "extended SO" approach with a burr hole at the keyhole; this modification is essentially the same as the skin incision and craniotomy used by us.…”
Section: Clinical Use Of So Versus Mp Routes Compared With Anatomical Studiesmentioning
confidence: 86%
“…Recent anatomical studies have compared the SO and MP routes to each other and to traditional pterional craniotomies. [19][20][21] However, with the exception of the systematic review by Rychen et al, no clinical series have compared these two approaches for brain tumors or assessed surgical field access and the anatomical regions that benefit from endoscopic visualization. 15 Herein, we report our experience using both approaches to treat over 200 brain tumor patients, with a focus on anatomical access visualized with MRI-based heatmaps, and document clinical outcomes.…”
mentioning
confidence: 99%
“…Hence, lesions located above the sphenoid ridge and near the midline are more suitable to be approached through shorter and more straightforward routes, such as a supraorbital or an extended supraorbital approach. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 11 ] Reports of large aneurysms treated through these small craniotomies are simply scarce. [ 6 , 7 , 9 ] In this manuscript, we present the technical nuances of a variation of the MPT approach, the extradural MPT approach (extMPTa) in the setting of a giant paraclinoid internal carotid artery (ICA) aneurysm.…”
Section: Introductionmentioning
confidence: 99%
“…There have been efforts made to quantify both approaches. 13,14 These publications have detailed surgical freedom as a 2D construct that is visually and methodologically interchangeable with the "area of exposure" metric. Studies have attempted to complete a 3D volumetric analysis.…”
Section: Vsf Advantagesmentioning
confidence: 99%